(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores pressing questions in the current education system: Which components of the educational load will retain their relevance in the coming decades, and which will soon become hopelessly outdated? What kind of correlation or boundary exists between specialized knowledge and the concept of "general culture"? How can general secondary education explain the integration between various disciplines? These and similar questions are at the center of active debates and discussions.